Petroleum coke desulfurization method
Through the photocatalytic technology of Fe3+ doped TiO2 and MOF-808 composite catalyst, the sulfides in petroleum coke are efficiently removed under normal temperature and pressure, solving the problems of low desulfurization efficiency, high energy consumption and poor catalyst stability in the existing technology, and achieving economical and environmentally friendly high-efficiency desulfurization effect.
Patent Information
- Application Number
- CN202510275454.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-04-25
AI Technical Summary
The existing petroleum coke desulfurization technology has low desulfurization efficiency, high energy consumption and poor catalyst stability, which cannot effectively solve the pollution problem of high sulfur content in petroleum coke.
Fe3+ doped TiO2 nanoparticles are used to recombinate with the metal organic frame material MOF-808 to form a composite catalyst, and efficient desulfurization is achieved through photocatalytic excitation at room temperature and pressure.
Under mild conditions, the removal efficiency of sulfide in petroleum coke is significantly improved, energy consumption is reduced, and the catalyst is stable and reusable, and it meets environmental protection requirements.
Smart Images

Figure BDA0005304071450000111 
Figure BDA0005304071450000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of petroleum coke desulfurization, in particular to a petroleum coke desulfurization method. Background Art
[0002] With the increase in energy demand, petroleum coke is widely used in the steel, aluminum and other industries as a low-cost energy raw material. However, petroleum coke usually contains a high sulfur content. These sulfides will produce a large amount of sulfur dioxide (SO2) during combustion, causing air pollution and environmental pollution, seriously affecting the ecological environment. Therefore, it is particularly important to develop an efficient, economical and environmentally friendly petroleum coke desulfurization technology.
[0003] At present, the desulfurization technologies for petroleum coke mainly include chemical methods, physical methods and catalytic methods. The chemical method usually relies on high temperature and strong oxidants to remove sulfides. Although the desulfurization effect is relatively significant, the high-temperature reaction not only consumes a lot of energy, but also may cause secondary pollution, which limits its application in industry. Although the physical method is easy to operate, its desulfurization efficiency is low and cannot meet the demand for high sulfur content in petroleum coke, and the treatment effect fluctuates greatly.
[0004] In recent years, photocatalysis has gradually become a promising desulfurization technology, especially in the design and optimization of catalysts. Although traditional photocatalysts, such as TiO2, have good photocatalytic performance, their catalytic efficiency is low. The main reason is that the band gap of the catalyst is large, and the photogenerated carriers are easy to recombine, resulting in unsatisfactory photocatalytic reaction effect. In addition, TiO2 has a small specific surface area and limited active sites, which also restricts its application in the desulfurization process.
[0005] In order to improve the photocatalytic desulfurization effect, researchers have tried to compound other materials with TiO2 to enhance its catalytic performance. MOF (metal organic framework) materials have gradually become a research hotspot because of their high specific surface area, rich pore structure and adjustable chemical properties. After MOF materials are compounded with TiO2, the photogenerated carrier separation efficiency of TiO2 can be effectively enhanced, thereby improving the catalytic activity. However, the existing MOF-based composite catalysts still have problems such as complex catalyst preparation process and unstable catalytic effect, which leads to unsatisfactory results in actual desulfurization applications.
[0006] Therefore, there is an urgent need to develop a catalytic desulfurization technology that can overcome the defects of the existing technology and improve the desulfurization efficiency. Summary of the invention
[0007] In view of the deficiencies of the prior art, the present invention provides a petroleum coke desulfurization method, which solves the problems of low desulfurization efficiency, high energy consumption and poor catalyst stability in the prior petroleum coke desulfurization technology.
[0008] To achieve the above objectives, the present invention is implemented through the following technical scheme: A method for desulfurization of petroleum coke, comprising the following steps:
[0009] Step 1, preparation of Fe 3+ Doped TiO2 nanoparticles;
[0010] In the first step, TiO2 powder is mixed with Fe 3+ The precursors react under controlled conditions to obtain Fe 3+ During the preparation process, the reaction temperature, time and TiO2 concentration were adjusted to make Fe 3+ It is uniformly doped into the TiO2 lattice, changing its light absorption characteristics and charge separation efficiency.
[0011] Fe 3+ The doping of Fe can introduce local energy levels into the TiO2 crystal structure, thereby narrowing the energy band width and enabling TiO2 to be effectively excited in the visible light range of 450-600nm. 3+ It helps to inhibit the recombination of electron-hole pairs and increase the lifetime of photogenerated carriers, which plays an important role in subsequent catalytic activity and efficient excitation of peroxymonosulfate to produce oxidative free radicals. This mechanism provides a technical basis for achieving efficient desulfurization under mild conditions.
[0012] Step 2: Fe 3+ The doped TiO2 nanoparticles are mixed with the metal organic framework material in a mass ratio of 1:1 to 5 to obtain a composite catalyst;
[0013] In this step, the prepared Fe 3+ Doped TiO2 nanoparticles and metal organic framework (MOF) materials are mixed in a mass ratio of 1:1 to 5. A proper amount of solvent (such as deionized water or other organic solvents) can be added during mixing, and the two components are ensured to form close contact on a microscopic scale through sufficient stirring and uniform dispersion, and further realize interface fusion in the subsequent hydrothermal treatment process to obtain a stable composite catalyst.
[0014] The MOF material itself has a high specific surface area and pore structure, which helps to disperse and fix TiO2 nanoparticles and form a multi-level pore structure, thereby improving the adsorption and diffusion rate of reactants (including sulfides and persulfates on the surface of petroleum coke). 3+ The heterojunction between doped TiO2 and MOF may be formed, which is beneficial to accelerate the separation and transmission of photogenerated carriers and further activate peroxymonosulfate to generate highly active oxidative free radicals (such as SO4· - ). This composite effect is a major innovation of the present invention, which enables the catalytic desulfurization process to achieve a high-efficiency catalytic effect at normal temperature and pressure.
[0015] Step 3, mixing petroleum coke powder with the composite catalyst and the peroxymonosulfate solution, irradiating the reaction system with visible light in the wavelength range of 450 to 600 nm, reacting at normal temperature and pressure to perform desulfurization treatment;
[0016] Finally, the petroleum coke powder to be desulfurized is mixed with the composite catalyst obtained in step 2 and the pre-prepared permonosulfate solution, and then placed in a reaction container. Under the irradiation of visible light in the wavelength range of 450 to 600 nm, the reaction is carried out at normal temperature and pressure, and the sulfide in the petroleum coke is converted into harmless or easily removable sulfur oxides by means of the photocatalytic excitation process and the oxidation of permonosulfate, thereby achieving the purpose of desulfurization.
[0017] Under visible light irradiation, Fe 3+ The doped TiO2 partially absorbs light energy to generate electrons and holes. The presence of the heterojunction in the composite catalyst further promotes the separation of photogenerated carriers and transfers electrons to the persulfate molecules adsorbed on the catalyst surface, reducing them to generate SO4 with strong oxidizing properties. - Free radicals. These free radicals have extremely high oxidizing power and can effectively oxidize organic sulfides in petroleum coke and reduce the sulfur content. The entire process can achieve efficient desulfurization under mild conditions, which is both energy-saving and environmentally friendly.
[0018] In addition, the introduction of the MOF structure not only provides excellent reactant transport and adsorption capabilities, but also may synergistically regulate the electronic state of the catalytic active center during the reaction, which is also the innovation of the present invention in the design of the catalytic system.
[0019] The innovation of the present invention is mainly reflected in the following aspects:
[0020] 1) Utilize Fe 3+ Doping TiO2 nanoparticles improves the light absorption range and carrier separation efficiency, achieving efficient excitation under visible light.
[0021] 2) By compounding with MOF materials, we can make full use of their high specific surface area and pore advantages to construct a heterojunction structure, further promoting reactant adsorption and carrier transport.
[0022] 3) The composite catalyst is used to effectively activate peroxymonosulfate under mild conditions to generate highly active oxidative free radicals, thereby achieving efficient oxidative removal of sulfides in petroleum coke.
[0023] Preferably, the preparation of Fe 3+ The steps of doping TiO2 nanoparticles include:
[0024] Step 1: Mix TiO2 powder with deionized water to obtain a TiO2 suspension with a concentration of 1 to 2 g / L. This step ensures that the TiO2 particles are evenly dispersed in water, which is beneficial for the subsequent Fe 3+ Uniform incorporation of ions.
[0025] The uniform dispersion of TiO2 suspension allows each nanoparticle surface to be exposed to the reaction medium, thus providing a 3+ The ions provide a uniform doping environment, which helps to form efficient photocatalytic active centers.
[0026] Step 2, dissolve Fe(NO3)3·9H2O in deionized water to obtain Fe 3+ Solution, concentration is 0.01M~0.1M; this concentration range can ensure that Fe 3+ The ions are sufficient and stable, and the Fe 3+ Excessive precipitation or formation of impurity phase.
[0027] Control Fe 3+ The concentration of the solution can precisely control the doping level to ensure that Fe 3+ It is embedded into the TiO2 crystal structure in appropriate proportions, thereby introducing suitable local energy levels in the TiO2 energy band, effectively expanding the light absorption range and improving the visible light response capability.
[0028] Step 3: Fe 3+ The solution is added to the TiO2 suspension and reacted at 100℃~120℃ for 6~12 hours. The hydrothermal treatment process makes Fe 3+ The ions migrate rapidly in a high temperature and high pressure environment and are incorporated into the TiO2 crystal structure to form Fe 3+ Doped TiO2 nanoparticles.
[0029] The hydrothermal reaction is Fe 3+ The uniform doping of Fe 3+ Ions can partially replace Ti 4 + ions, forming energy level defects and local band bending, thereby effectively narrowing the band gap of TiO2. This process not only enhances the absorption capacity of TiO2 in the visible light band, but also helps to inhibit the recombination of photogenerated electron-hole pairs, significantly improving the catalytic reaction efficiency. This doping achieved by hydrothermal reaction is an innovation of the present invention in material preparation technology, laying the foundation for subsequent efficient desulfurization applications.
[0030] Preferably, the metal organic framework (MOF) material is MOF-808. MOF-808 is a metal organic framework material formed by a Zr (zirconium) metal center and an organic ligand through a coordination bond. Its unique structural characteristics include high specific surface area, large pore size and high adjustability, which makes it have important application value in the fields of catalysis, adsorption and gas storage.
[0031] Due to its highly ordered pore structure and large specific surface area, MOF-808 can provide abundant surface active sites, which is conducive to the adsorption and diffusion of catalytic reactants. In the desulfurization reaction, these characteristics of MOF-808 enable it to effectively adsorb and stabilize reactants (such as sulfides in petroleum coke and sulfur sources in persulfate solutions), enhancing the efficiency of the catalytic reaction. In addition, the metal center (Zr) of MOF-808 plays a positive role in the transfer of electrons and the guidance of photogenerated carriers, thereby enhancing the catalytic performance.
[0032] In the present invention, MOF-808 and Fe 3+ The doped TiO2 nanoparticles are composited to form a composite catalyst. The introduction of MOF-808 not only increases the specific surface area and porosity of the catalyst, but also has a synergistic effect with TiO2 nanoparticles, thereby optimizing the photocatalytic reaction process, especially in the transfer of photogenerated electrons and the separation of photogenerated carriers. The innovation of this composite material lies in its ability to achieve efficient desulfurization of petroleum coke under mild reaction conditions (normal temperature and pressure).
[0033] Preferably, the synthesis steps of the metal organic framework material include:
[0034] Step 1: dissolve 1,3,5-benzenetricarboxylic acid and ZrCl4 in N,N-dimethylformamide (DMF) at a mass ratio of 1:1 to 3 to obtain a uniform precursor solution.
[0035] As a polar organic solvent, DMF can not only fully dissolve 1,3,5-benzenetricarboxylic acid and ZrCl4, but also participate in the coordination process through intermolecular interactions. 4+ The initial coordination bonds are formed between the ions, laying the foundation for the subsequent self-assembly of the crystal. By adjusting the ratio of the reactants in the solution, the coordination environment between the metal and the organic ligand can be optimized, thereby ensuring the uniformity of the generated precursor and providing favorable conditions for the formation of high-quality crystals.
[0036] Step 2: Transfer the precursor solution to a hydrothermal reactor and react at a temperature range of 120° C. to 130° C. for 12 to 24 hours to obtain a metal organic framework material crystal.
[0037] Under hydrothermal conditions, the high temperature and high pressure environment promotes the coordination units in the precursor solution to fully self-assemble and gradually form crystals with long-range ordered structures. 4+ A stable coordination network is formed between the center and the organic ligand, thereby constructing a MOF crystal with a high specific surface area and ordered pores. The formed metal organic framework not only has excellent thermal and chemical stability, but also its porous structure is conducive to the adsorption and diffusion of catalytic reactants, which can significantly improve the catalytic efficiency in the subsequent catalytic desulfurization process.
[0038] Preferably, the preparation steps of the composite catalyst include:
[0039] Step 1: Fe 3+ The doped TiO2 nanoparticles and MOF-808 are mixed in a mass ratio of 1:2 to 4, and an appropriate amount of deionized water is added, and the mixture is fully stirred to achieve uniform dispersion.
[0040] In this step, uniform mixing ensures that Fe 3+ Doped TiO2 nanoparticles can be evenly distributed in the pores and surface of MOF-808 to form a good contact interface. Deionized water as a dispersion medium helps to reduce the agglomeration of particles and promote the effective fusion of the two components. Due to its high specific surface area and rich pore structure, MOF-808 can provide an effective carrier for TiO2, which is conducive to the formation of heterojunctions, improve the separation efficiency of photogenerated carriers, and provide favorable conditions for the subsequent photocatalytic activation of peroxymonosulfate.
[0041] Step 2, transferring the mixture to a hydrothermal reactor, and performing a hydrothermal reaction at a temperature range of 150°C to 180°C for 24 to 48 hours to finally obtain a stable composite catalyst Fe 3+ Doped TiO2@MOF-808.
[0042] Under hydrothermal reaction conditions, high temperature and high pressure help promote Fe 3+ The interface between doped TiO2 and MOF-808 fuses to form a strong composite structure. This process not only helps to further improve the contact efficiency between TiO2 and MOF in the catalyst, but also forms an electron transmission channel at the interface, enhancing the separation and transfer efficiency of photogenerated carriers (electrons and holes). Such a stable and highly synergistic composite catalyst performs well in activating peroxymonosulfate to generate highly active oxidative free radicals, thereby improving the overall efficiency of the petroleum coke desulfurization reaction.
[0043] Preferably, the reaction conditions of the reaction system include: light intensity of 100 mW / cm 2 ~200mW / cm 2, and the irradiation time is 2 hours to 4 hours. These conditions have been optimized to ensure that the composite catalyst can fully exert its photocatalytic activity under visible light excitation, achieve efficient activation of peroxymonosulfate and generate highly active oxidative free radicals, thereby effectively removing sulfides from petroleum coke.
[0044] Light intensity at 100mW / cm 2 ~200mW / cm 2 Within the range of the composite catalyst Fe 3+ Doping TiO2@MOF-808 obtains sufficient light energy, thereby generating a large number of photogenerated electrons and holes at the interface of TiO2 and MOF. Appropriate light intensity can not only excite a sufficient number of photogenerated carriers, but also avoid overheating of the catalyst surface or accelerated carrier recombination rate caused by excessive light intensity, thus ensuring the stability and efficiency of the overall reaction.
[0045] The irradiation time is set within 2 to 4 hours, which can not only ensure that the reaction system reaches reaction equilibrium under continuous stimulation, but also help avoid unnecessary energy waste or catalyst performance degradation caused by too long irradiation. This time range has been optimized through experiments, which can effectively activate peroxymonosulfate to generate highly oxidizing SO4. - Free radicals, thereby quickly oxidizing the sulfides in petroleum coke.
[0046] Through the optimized combination of light intensity and irradiation time, the present invention utilizes the photocatalytic mechanism to achieve efficient desulfurization under normal temperature and pressure conditions.
[0047] Preferably, the pH value of the reaction system is controlled at 6.0 to 8.0. This pH range is in the neutral to weakly alkaline range, which helps to maintain the stability of the composite catalyst and efficiently activate peroxymonosulfate, thereby promoting the effective oxidation removal of sulfide.
[0048] In the pH range of 6.0 to 8.0, the surface charge state of the composite catalyst is more stable, avoiding the corrosion or precipitation of the catalyst surface that may occur under over-acid or over-alkaline conditions, thereby ensuring its long-term and efficient operation. It can also ensure that peroxymonosulfate is effectively converted into SO4 with strong oxidizing ability. - Free radicals are generated, thereby improving the desulfurization efficiency. At the same time, under neutral to weakly alkaline conditions, the separation efficiency of photogenerated electrons and holes in the photocatalytic process is high, which is beneficial to reduce carrier recombination and improve the overall catalytic activity.
[0049] Preferably, the concentration of the peroxymonosulfate solution is 3-5 mM, and the volume ratio of the peroxymonosulfate solution in the reaction system is 2%-5%. This setting can ensure that there is enough peroxymonosulfate in the reaction system to participate in the reaction, and can also avoid excessive use of peroxymonosulfate to cause side reactions, thereby efficiently stimulating the generation of SO4· with strong oxidizing ability under visible light irradiation.- Free radicals can effectively oxidize and remove sulfides in petroleum coke.
[0050] Preferably, the mass ratio of the petroleum coke powder to the composite catalyst is 10 to 5:1, that is, 1 part of the composite catalyst is added for every 10 to 5 parts of petroleum coke powder, in order to balance the amount of the catalyst and the desulfurization reaction efficiency.
[0051] The present invention provides a petroleum coke desulfurization method having the following beneficial effects:
[0052] 1. The method of the present invention optimizes the reaction conditions and adopts Fe 3+ Doped TiO2@MOF-808 composite catalyst can efficiently stimulate the generation of SO4 in a short time. - Free radicals are generated, thereby achieving rapid oxidation and removal of organic sulfides in petroleum coke and significantly improving the desulfurization efficiency.
[0053] 2. The present invention utilizes visible light to stimulate the catalytic reaction, which not only avoids the use of high temperature and high pressure conditions, but also allows the entire reaction process to be carried out at room temperature and pressure, reducing energy consumption. At the same time, the reaction system has no secondary pollution, meets the requirements of green environmental protection, and has good environmental friendliness.
[0054] 3. Through Fe 3+ Due to the synergistic effect of doping and MOF-808 support, the composite catalyst prepared by the present invention exhibits excellent photocatalytic activity and carrier separation efficiency, and at the same time forms a stable interface structure under the hydrothermal treatment process, ensuring the high efficiency and reusability of the catalyst during long-term use.
[0055] 4. The method of the present invention adopts hydrothermal synthesis and simple mixing and stirring process, does not require complex equipment or expensive reagents, has a simple operation process and is easy to scale up. Due to mild reaction conditions and low energy consumption, the overall cost can be effectively controlled, thus having good economic benefits.
[0056] 5. The scheme of the present invention is highly controllable in terms of reaction conditions and catalyst ratios. The parameters can be flexibly adjusted according to the sulfur content and process requirements of different petroleum coke raw materials to meet the desulfurization needs of different scales and types, showing good prospects for application and promotion. DETAILED DESCRIPTION
[0057] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0058] Embodiment 1:
[0059] 1. Synthesis of MOF-808
[0060] Precursor preparation: 1,3,5-benzenetricarboxylic acid and ZrCl4 were dissolved in N,N-dimethylformamide at a mass ratio of 1:1.5 to form a uniform precursor solution.
[0061] Hydrothermal reaction: The precursor solution was transferred to a hydrothermal reactor and reacted at 125°C for 18 hours to obtain MOF-808 crystals.
[0062] 2. Composite catalyst Fe 3+ Preparation of doped TiO2@MOF-808
[0063] Mixing step: Fe 3+ The doped TiO2 nanoparticles were mixed with the prepared MOF-808 in a mass ratio of 1:3, and an appropriate amount of deionized water was added and stirred thoroughly.
[0064] Hydrothermal treatment: The mixture was transferred to a reactor and subjected to hydrothermal reaction at 160°C for 36 hours to obtain a composite catalyst Fe 3+ Doped TiO2@MOF-808.
[0065] 3. Desulfurization reaction conditions
[0066] Light conditions: Light intensity was set to 150 mW / cm 2 , irradiation time 3 hours.
[0067] Reaction system: pH was controlled at 7.0, the concentration of permonosulfate solution was 4 mM, and the volume ratio in the system was 3%.
[0068] Material ratio: The mass ratio of petroleum coke powder to composite catalyst is set to 8:1.
[0069] Embodiment 2:
[0070] 1. Synthesis of MOF-808
[0071] Precursor preparation: 1,3,5-benzenetricarboxylic acid and ZrCl4 were dissolved in DMF at a mass ratio of 1:2 to form a stable precursor solution.
[0072] Hydrothermal reaction: The reaction was carried out at 130°C for 24 hours to obtain MOF-808 with a relatively complete crystal morphology.
[0073] 2. Composite catalyst Fe 3+ Preparation of doped TiO2@MOF-808
[0074] Mixing steps: Fe 3+ Doped TiO2 nanoparticles were mixed with MOF-808, and deionized water was added and stirred thoroughly to ensure full contact between the two.
[0075] Hydrothermal treatment: The composite catalyst was synthesized by performing a hydrothermal reaction at 150°C for 24 hours.
[0076] 3. Desulfurization reaction conditions
[0077] Light conditions: Set the light intensity to 100mW / cm 2 , the irradiation time is 2.5 hours.
[0078] Reaction system: pH value was controlled at 6.5, peroxymonosulfate concentration was set at 3 mM, and the volume ratio was 2.5%.
[0079] Material ratio: The mass ratio of petroleum coke powder to composite catalyst is adjusted to 10:1.
[0080] Embodiment 3:
[0081] 1. Synthesis of MOF-808
[0082] Precursor preparation: 1,3,5-benzenetricarboxylic acid and ZrCl4 were dissolved in DMF at a mass ratio of 1:1 to obtain a high-concentration precursor solution.
[0083] Hydrothermal reaction: The hydrothermal reaction was carried out at 120 °C for 12 h to rapidly form MOF-808 crystals, and the crystal size was controlled within the nanoscale range to increase the surface area.
[0084] 2. Composite catalyst FeFe 3+ Preparation of doped TiO2@MOF-808
[0085] Mixing steps: FeFe 3+ The doped TiO2 nanoparticles and MOF-808 were mixed in a mass ratio of 1:2, and an appropriate amount of deionized water was added and stirred evenly.
[0086] Hydrothermal treatment: Hydrothermal reaction was carried out at 180°C for 48 hours to ensure the formation of a close interface between the two components in the composite catalyst.
[0087] 3. Desulfurization reaction conditions
[0088] Light conditions: Light intensity set to 200mW / cm 2 , irradiation time 4 hours.
[0089] Reaction system: pH was controlled at 8.0, the peroxymonosulfate concentration was 5 mM, and the volume ratio was 5%.
[0090] Material ratio: The mass ratio of petroleum coke powder to composite catalyst is set to 5:1 to increase the reaction rate.
[0091] Comparative Example 1:
[0092] Compared with Example 1, the difference is that undoped Fe 3+ TiO2 nanoparticles replace Fe 3+ Doped TiO2 nanoparticles, the rest are the same.
[0093] Comparative Example 2:
[0094] Compared with Example 1, the difference is that the visible light irradiation step is eliminated, that is, no light energy is applied during the entire reaction process, and the rest is the same.
[0095] Comparative Example 3:
[0096] Compared with Example 2, the difference is that the MOF-808 support is completely removed and only Fe 3+ The reaction was carried out with doped TiO2 nanoparticles, and the rest was the same.
[0097] Comparative Example 4:
[0098] Compared with Example 2, the difference is that the hydrothermal reaction step is eliminated, and the stirring reaction is directly carried out at room temperature after mixing, and the rest is the same.
[0099] Comparative Example 5:
[0100] Compared with Example 3, the difference is that the MOF-808 with a high specific surface area is replaced by a Zr-based material with a low specific surface area, and the rest are the same.
[0101] Comparative Example 6:
[0102] Compared with Example 3, the difference is that the hydrothermal treatment is cancelled, and the high-temperature reaction in the composite catalyst preparation step is replaced by mixing and stirring at room temperature, and the rest is the same.
[0103] Test example:
[0104] The sulfur content in petroleum coke samples was quantitatively determined using a CLS-3000 microcoulometric sulfur analyzer. To ensure the reliability of the experimental data, all petroleum coke samples were dried and fully homogenized before testing.
[0105] In the pretreatment stage, the initial sulfur content of the petroleum coke samples of Examples 1 to 3 and Comparative Examples 1 to 6 was measured respectively. The results showed that the initial sulfur content of each sample was within the range of 5.25 wt% ± 0.07 wt%.
[0106] Subsequently, the samples were subjected to desulfurization reaction according to the desulfurization process conditions set for each sample. After the reaction was completed, the samples were cooled and post-processed as necessary, and the sulfur content was measured again using the CLS-3000 microcoulomb sulfur analyzer. The final sulfur content data after desulfurization is shown in Table 1:
[0107] Table 1:
[0108]
[0109]
[0110] It can be seen from the data in Table 1 that the three groups of embodiments all show obvious advantages in desulfurization effect. Among them, Example 3 obtains the highest sulfur removal rate (80%) under the conditions of optimizing light intensity, reaction time, pH control and peroxymonosulfate concentration, while Example 1 and Example 2 achieve desulfurization effects of 65.7% and 60.0%, respectively.
[0111] This test case further verifies the importance of each key parameter:
[0112] Comparative Example 1 (Undoped Fe 3+ The results of Example 3 (without TiO2) and Comparative Example 3 (without MOF-808 support) show that the undoped TiO2 and the lack of high specific surface area support material will lead to a significant decrease in sulfur removal rate (only 33.3% and 40.0%, respectively), proving that Fe 3+ Doping and MOF-808 support play a key role in forming an efficient catalytic interface and promoting the separation of photogenerated carriers.
[0113] When the high specific surface area MOF-808 is replaced by the low specific surface area Zr-based material in Comparative Example 5, the desulfurization effect is similar to that in Example 3, but overall, the high specific surface area material helps to further improve the reaction activity and ensure the dispersion of the catalyst and the exposure of the active sites.
[0114] In Comparative Example 2, the visible light irradiation was cancelled, resulting in a desulfurization rate of only 6.7%, indicating that light energy excitation is the main factor in generating highly active oxidative free radicals (SO4· - ) is a necessary condition.
[0115] In Comparative Examples 4 and 6, eliminating or reducing the hydrothermal treatment step significantly reduced the desulfurization effect (only 23.8% and 27.6%, respectively), which shows that hydrothermal treatment helps to form a tight interface structure in the preparation of the composite catalyst, promotes the effective reaction of photogenerated electrons with peroxymonosulfate, and thus improves the generation efficiency of free radicals.
[0116] In the above test example, Fe 3+The doped TiO2@MOF-808 composite catalyst, under visible light irradiation, TiO2 is excited to produce electron-hole pairs. 3+ Doping not only reduces the band gap of TiO2, but also effectively promotes carrier separation, while the high specific surface area and pore structure of MOF-808 provide more reaction sites and excellent mass transfer conditions. At this time, the persulfate added to the reaction system generates SO4 with extremely strong oxidizing ability under the action of photogenerated electrons. - Free radicals can quickly oxidize organic sulfides in petroleum coke to achieve efficient desulfurization.
[0117] In the comparative experiment, when the key components (such as Fe 3+ When the doping or MOF-808 support) is removed, or the key energy input (light irradiation, hydrothermal treatment) is cancelled, the photogenerated carriers in the system cannot be effectively separated, resulting in a significant reduction in the generation of active free radicals, which in turn causes a significant decrease in the desulfurization efficiency.
[0118] In general, the data and comparative examples fully demonstrate that in the technical scheme of the present invention, the synergistic effect of various key parameters and material compositions in the desulfurization reaction is the core to achieve efficient desulfurization, and its mechanism mainly relies on photocatalytic excitation, carrier separation and efficient active free radical generation, thus providing an economical, environmentally friendly and efficient technical path for petroleum coke desulfurization.
[0119] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for desulfurization of petroleum coke, characterized in that: The following steps are involved: a) Preparation of Fe 3+ Doped TiO2 nanoparticles; b) Fe 3+ The doped TiO2 nanoparticles are mixed with the metal organic framework material in a mass ratio of 1:1 to 5 to obtain a composite catalyst; c) mixing petroleum coke powder with the composite catalyst and peroxymonosulfate solution, irradiating the reaction system with visible light in the wavelength range of 450 to 600 nm, and reacting at normal temperature and pressure to perform desulfurization treatment.
2. The method for desulfurization of petroleum coke according to claim 1, characterized in that: The preparation of Fe 3+ The steps of doping TiO2 nanoparticles include: Mixing TiO2 powder with deionized water to obtain a TiO2 suspension; Dissolve Fe(NO3)3·9H2O in deionized water to obtain Fe 3+ Solution, concentration 0.01M~0.1M; Fe 3+ The solution is added to the TiO2 suspension and reacted under hydrothermal conditions at 100℃~120℃ for 6~12 hours to obtain Fe 3+ Doped TiO2 nanoparticles.
3. The method for desulfurization of petroleum coke according to claim 2, characterized in that: The concentration of the TiO2 suspension is 1-2 g / L.
4. The method for desulfurization of petroleum coke according to claim 1, characterized in that: The metal organic framework material is MOF-808.
5. The method for desulfurization of petroleum coke according to claim 1, characterized in that: The synthesis steps of the metal organic framework material include: Dissolve 1,3,5-benzenetricarboxylic acid and ZrCl4 in N,N-dimethylformamide at a mass ratio of 1:1 to 3 to obtain a precursor solution; The precursor solution is transferred to a hydrothermal reactor and reacted at a temperature range of 120° C. to 130° C. for 12 to 24 hours to obtain a metal organic framework material crystal.
6. The method for desulfurization of petroleum coke according to claim 1, characterized in that: The preparation steps of the composite catalyst include: Fe 3+ Doped TiO2 nanoparticles and MOF-808 were mixed in a mass ratio of 1:2 to 4, deionized water was added, and stirred evenly; The mixture was transferred to a hydrothermal reactor and subjected to a hydrothermal reaction at a temperature range of 150°C to 180°C for 24 to 48 hours to obtain a composite catalyst Fe 3+ Doped TiO2@MOF-808.
7. The method for desulfurization of petroleum coke according to claim 1, characterized in that: The reaction conditions of the reaction system include: light intensity of 100 mW / cm 2 ~200mW / cm 2 The irradiation time is 2 hours to 4 hours.
8. The method for desulfurization of petroleum coke according to claim 1, characterized in that: The pH value of the reaction system is controlled at 6.0-8.
0.
9. The method for desulfurization of petroleum coke according to claim 1, characterized in that: The concentration of the peroxymonosulfate solution is 3-5 mM, and the volume ratio of the peroxymonosulfate solution in the reaction system is 2%-5%.
10. The method for desulfurization of petroleum coke according to claim 1, characterized in that: The mass ratio of the petroleum coke powder to the composite catalyst is 10 to 5:1.